Intergenerational Social Conflict in Indonesian Migrant Worker Families - Andhita Risko Faristiana (Jurnal Ilmu Sosial dan Humaniora, 2025)
Intergenerational social conflict in Indonesian migrant worker families represents a critical yet underexamined structural phenomenon that fundamentally disrupts family functioning, individual well-being, and cultural value transmission across multiple generations. This systematic literature review aims to comprehensively synthesize empirical evidence on the causal determinants, manifestation patterns, multidimensional impacts, and resolution strategies of intergenerational conflicts in Indonesian migrant worker families between 2020-2025. Following PRISMA guidelines, literature searches were conducted across Scopus, Web of Science, ProQuest, JSTOR, ScienceDirect, and Indonesian repositories (Garuda, Indonesia OneSearch). Initial identification yielded 309 articles; after duplicate removal, screening, and quality appraisal using CASP criteria, 28 high-quality peer-reviewed articles were systematically analyzed using NVivo 12 thematic analysis. Results reveal that conflicts emerge from boundary ambiguity caused by parental absence, communication disruptions intensified by Indonesian "halus" communication styles, and economic tensions reflecting divergent generational worldviews shaped by distinct historical experiences. Conflicts manifest through explicit financial disputes and latent role ambiguities, systematically undermining family resilience across legal-integrity, physical, socio-psychological, and socio-cultural dimensions while disrupting traditional value transmission and creating "intimate isolation" despite physical family proximity. Families employ culturally-specific adaptation strategies including accommodation approaches, spirituality-based coping through Islamic values, and economic diversification, though structural barriers limit effectiveness. Two critical interventions are recommended: developing holistic, culturally-sensitive migrant worker protection policies incorporating pre-departure family preparation programs, accessible remittance frameworks, and gender-specific provisions; and strengthening community-based family counseling services through culturally-appropriate conflict mediation training, intergenerational financial literacy programs, and accessible legal aid addressing migration-related disputes.